(untitled) (Abrahamic Religions: Jurnal Studi Agama-Agama, 2026)
This study discusses the background of the theological polemic concerning the authority of the Bible, which is simultaneously viewed as the highest divinely inspired text and a human document containing internal contradictions and historical inconsistencies. This study aims to analyse the influential perspective of Swiss theologian Karl Barth as a resolution to this tension. Its main objectives are to investigate Barth’s conceptualisation of the polemic surrounding biblical truth and to examine his critique of biblical inerrancy. This study uses a qualitative method with a theological approach, conducting a systematic literature review of Barth’s major works, academic journals, and related documentation. The results show that Barth affirms the Bible not as the perfect and direct Word of God, but as a fallible human ‘witness’ to the true Word, Jesus Christ. This study concludes that Barth’s position avoids rejecting the Bible by affirming that the text becomes the Word of God dynamically through divine-human encounters, rather than having static inerrancy. The specific theological contribution of this research, in addition to the existing scholarship, is the articulation of Barth’s dialectical framework as a powerful ‘third way’ that transcends the impasse between fundamentalist literalism and liberal revisionism, thereby promoting a coherent understanding of the sacredness of scripture in contemporary Christianity